Accelerated Infliximab Dosing Increases 30-Day Colectomy in Hospitalized Ulcerative Colitis Patients: A Propensity Score Analysis. Issue 3 (16th February 2018) - Shah, Shailja C; Naymagon, Steven; Panchal, Hinaben J; Sands, Bruce E; Cohen, Benjamin L; Dubinsky, Marla C
Abstract: Background: Standard outpatient induction dosing of infliximab (IFX) may not be effective in hospitalized ulcerative colitis (UC) patients with higher inflammatory burden and colectomy risk. Our aim was to determine whether initial IFX induction dose affects 30-day colectomy rate and other disease-related outcomes. Methods: IFX-naive hospitalized UC patients receiving at least 1 inpatient 5 mg/kg (SD) or 10 mg/kg (HD) IFX induction dose were included. Baseline demographics and admission-related characteristics were documented. Propensity score based matching was used to control for provider bias introduced due to nonprotocolized choice of IFX dose. The primary outcome was 30-day colectomy; secondary outcomes included the need for an accelerated induction IFX (AD), length of stay (LOS), 90-day and 1-year colectomy, and complications. Results: Of 146 (120 SD/26 HD) patients included, 25 (17.1%) underwent colectomy by 30 days, 33 (22.6%) by 90 days, and 41 (28.1%) by 1 year. In 21 propensity score matched dyads (n = 42) treated with SD or HD, colectomy rates and LOS were similar. SD patients more often needed AD (23.8% vs. 0%, P = 0.048) and AD patients progressed to colectomy more rapidly within 30 days compared to non-AD ( P = 0.001). Female sex and hypoalbuminemia were associated with significantly increased odds of needing AD on both univariate and multivariate analyses. Conclusions: In our propensity score based analysis, receiving accelerated IFX dosing after an initial SD infusion was associated with significantly higher 30-day colectomy rates in hospitalized acute UC patients. The most effective dosing strategy in this population remains unclear and prospective randomized studies are needed.